Validasi Psikometrik Asesmen Kesiapan Kerja Psikologis bagi Mahasiswa Vokasi. - Dwilanisusantya, Carissa; Ananto, Purnomo (Indonesian Psychological Research, 2026)
The increasing complexity of contemporary workplaces requires vocational graduates to possess not only technical competencies but also psychological readiness to adapt and function effectively in professional environments. However, psychometrically validated instruments specifically designed to assess psychological work readiness among vocational higher education students remain limited. This study aimed to develop and validate the Psychological Work Readiness Assessment (PWRA), a multidimensional instrument designed to measure psychological readiness for workplace transition among vocational students. A total of 222 vocational higher education students participated in the study. Data were analyzed using Confirmatory Factor Analysis (CFA) to evaluate the proposed five-factor structure consisting of Adaptability, Emotional Regulation, Collaboration, Professional Responsibility, and Self-Confidence. The results indicated that all indicators loaded significantly on their respective constructs (p < .001), with standardized factor loadings ranging from .542 to .794. The measurement model demonstrated acceptable fit, with CFI = .824, TLI = .806, SRMR = .078, and RMSEA = .087. Composite Reliability values ranged from .82 to .86, while Average Variance Extracted values ranged from .44 to .51. Overall, the findings provide preliminary evidence supporting the validity and reliability of the PWRA as an instrument for assessing psychological work readiness among vocational higher education students. The instrument has potential applications in student assessment, employability development programs, career preparation initiatives, and educational planning within vocational education settings.